Acupuncture Ameliorates Depressive Behaviors by Modulating the Expression of Hippocampal Iba-1 and HMGB1 in Rats Exposed to Chronic Restraint Stress - Chen, Lu; Jiang, Huili; Bao, Tuya; Wang, Yu; Meng, Hong; Sun, Yang; Liu, Pengfei; Quan, Songxiao; Li, Wenshan; Qi, Simin; Ren, Xiujun (Frontiers in Psychiatry, 2022)
The antidepressant mechanism of acupuncture has not been fully elucidated recently. Thus, the objective of the present study is to investigate the antidepressant mechanism of acupuncture of modulating the neuroinflammation induced by high mobility group box-1 (HMGB1) in rats subjected to chronic restraint stress (CRS). Forty-four male Sprague Dawley rats were randomly divided into control, model, escitalopram, and acupuncture group. Except for rats in the control group, all rats were exposed to CRS for 21 days continuously. Rats in the escitalopram group were subjected to a suspension of escitalopram and saline. One hour before CRS procedures, acupuncture was performed at Baihui (GV20) and Yintang (GV29) for rats in the acupuncture group, 20 minutes per day for 21 days. All rats in each group were conducted to detect the body weight, sucrose preference test at 0, 7, 14, 21 days to evaluate the depression-like behaviors. The expression of microglial activation and HMGB1 in the hippocampus was detected by immunofluorescence. The expression of hippocampal interleukin-10 (IL-10) was detected by western blot. And the content of serum tumor necrosis factor-α (TNF-α) was detected by the enzyme-linked immunosorbent assay method. CRS-exposed rats showed obviously decreased body weight and sucrose preference when compared with the control group, which was reversed by acupuncture. The results have also shown that acupuncture ameliorated the CRS-induced activation of microglia and HMGB1 in the hippocampus CA1 region. Furthermore, acupuncture reduced the stress-induced upregulation of TNF-α in serum. Collectively, the current study highlights the role of acupuncture in alleviating depressive behavior associated with stress-induced neuroinflammation mediated by HMGB1 in the CRS model of depression.